Analisis Kinerja Keuangan PT Bumi Serpong Damai Tbk Pada Sektor Properti dan Real Estate di Bursa Efek Indonesia: Studi Rasio Keuangan 2019-2024 - Dandi Aprila; Ranila Suciati; Ni Komang Maysarah Darapalgia (Politeknik Negeri Padang, 2026)
This study is motivated by the limited number of studies that examine longitudinal changes in the financial performance of property companies, particularly in the post–COVID-19 period. Despite its strategic role in the national economy through its contribution to Gross Domestic Product (GDP) and its strong linkages with related sectors such as construction, banking, and building materials, empirical evidence on firm-level financial dynamics in this sector remains scarce. This study aims to analyze the financial performance of PT Bumi Serpong Damai Tbk (BSDE) during the 2019–2024 period using financial ratio analysis, including liquidity, solvency, activity, profitability, and market ratios. The study employs a descriptive quantitative approach with a single-firm case design. BSDE was purposively selected based on the availability and completeness of its published financial statements. The data were obtained from annual financial reports released by the Indonesia Stock Exchange, supported by macroeconomic data from Bank Indonesia and Statistics Indonesia. The analysis was conducted through the calculation of financial ratios and trend interpretation over a six-year observation period. The results indicate that BSDE’s financial performance experienced fluctuations during the pandemic period but showed a significant recovery after 2022. Profitability and market ratios improved, while liquidity and solvency ratios reflected a strengthening of the company’s capital structure. These findings highlight the importance of balanced financing decisions and asset efficiency in maintaining corporate financial stability. This study provides practical insights for investors and policymakers in assessing the resilience of Indonesia’s property sector.